Peningkatan Hasil Belajar Bahasa Indonesia Materi Struktur Teks Deskripsi melalui Model Kooperatif Tipe Make A Match Siswa Kelas VII SMP Negeri 001 Sentajo Raya - Familza, Tri (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Islam Riau, 2018)
The results of learning Indonesian in the seventh grade students of SMP Negeri 1 Sentajo Raya still do not meet expectations. Therefore, it is necessary to conduct classroom action research to improve the learning. Improvement of learning is done using the Make a Match learning method. This Classroom Action Research aims to obtain factual information about the use of the Make a Match learning method in improving student learning outcomes. Classroom Action Research Procedures carried out through a grooved process consisting of 4 stages, namely: 1) planning; 2) implementation; 3) observation; and 4) reflection. From the data analysis it is known that in each cycle there is an increase in the completeness of student learning outcomes. In the initial study, students who achieved new completeness were 29.2%. In the first cycle students who achieved completeness increased to 58.3%. In cycle II students who achieved completeness experienced an increase to 83.3%. The same thing happens to student learning activities. Based on the results of this study it can be concluded that the use of the learning method of Make a Match can improve the learning outcomes of Indonesian students of class VII Sentajo Raya 1 Public Middle School.